INCLUSIVE ELEMENTARY SCHOOL EXPECTATIONS UNIVERSITY ENGAGEMENT: INCLUSIVE EDUCATION PRACTICES IN INDONESIA: Received: 15th September 2021; Revised: 20th December 2021, 03rd January 2022, 09th January 2022; Accepted: 10th January 2022 - Rasmitadila, .; Humaira, Megan Asri; Rachmadtullah, Reza; Putri, Ayu Anggraini (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The involvement of universities in inclusive education in inclusive elementary schools is still not maximal, and the real impact can be felt for improving the quality of inclusive primary schools. This study aims to explore the opinion of general teachers (GT) on the expectations of university involvement in inclusive education practices in Indonesia. Data were collected using semi-structured interviews of forty GTs in two provinces in Indonesia. Data were analyzed using thematic analysis. The research resulted in three main themes: inclusive school mentoring, majors relevant to inclusive education in universities, and students’ understanding in an inclusive classroom. Universities must meet the needs of elementary school graduates who will teach inclusive classrooms based on the problems faced by GTs so far, including academic and non-academic aspects. The results of this research are significant for universities to design courses that are relevant and in line with the needs of inclusive elementary schools. For this reason, all decision-makers at the university must be able to make and establish rules following the analysis of the needs of inclusive education practices.